2020
DOI: 10.19184/pk.v7i1.17591
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Sanitasi Lingkungan dengan Kejadian Infeksi Soil Transmitted Helminths pada Anak Sekolah Dasar di Jember

Abstract: Poor environmental sanitation is suspected to be one of the causes of soil transmitted helminthes (STH) infection. Environmental sanitation consists of water sources, latrine, sewerage, garbage disposal facilities, and floor type. The objective of this study was to investigate the relationship between environmental sanitation and the incidence of STH infection in primary school children. This was an observational analytic study with cross-sectional design. The subjects were 80 students of two elementary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
4
0
9
Order By: Relevance
“…Research conducted by Baidowi et al (2019) also showed a significant association between PPE use and STH infection status, so it is important to study it. Questions regarding environmental sanitation in this study are also less comprehensive, for example, not asking about waste disposal facilities and wastewater disposal channels (SPAL) (Kusumawardani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Baidowi et al (2019) also showed a significant association between PPE use and STH infection status, so it is important to study it. Questions regarding environmental sanitation in this study are also less comprehensive, for example, not asking about waste disposal facilities and wastewater disposal channels (SPAL) (Kusumawardani, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Kondisi sanitasi yang tidak memnuhi syarat tersebut memiliki hubungan dengan angka kejadian infeksi STH. 24 Tidak hanya pada anak-anak, kondisi sanitasi yang buruk yang akan meningkatakan resiko infeksi STH juga dapat berdampak pada orang dewasa. Bahkan kondisi infeksi STH ini dapat semakin memperburuk kondisi penderita jika penderita sudah memiliki penyakit infeksi sebelumnya, sehingga STH ini akan menjadi coinfeksi dengan penyakit infeksi lainnya.…”
Section: Peran Sanitasi Dalam Pencegahan Infeksi Sthunclassified
“…Hasil Penelitian Kusumawardani et al, 2019 [34] Tidak terdapat hubungan bermakna antara kejadian infeksi STH dengan sanitasi lingkungan (p= 0.165). Sofiana et al, 2020 [35] Tidak terdapat hubungan bermakna antara infeksi STH dengan kepadatan lalat (sig= 0.307), Tempat Pembuangan Akhir (sig= 0.207), jenis lantai (sig= 0.330).…”
Section: Sanitasi Nama Penulisunclassified
“…Penelitian yang dilakukan siswa SD di Jember menunjukkan tidak adanya hubungan bermakna antara kejadian infeksi STH dengan sanitasi lingkungan (p = 0.165) [34]. Lebih lanjut, tidak ditemukan adanya hubungan antara sanitasi dengan kejadian infeksi STH juga ditemukan pada penelitian yang dilakukan anak usia sekolah dasar di Puskesmas Moyudan dengan variabel yang diukur yaitu, kepadatan lalat (sig=0.348), ketersediaan toilet (sig = 0.307), Tempat Pembuangan Akhir (TPA) (sig = 0.207), jenis lantai (sig = 0.330) [35].…”
Section: Sanitasi Nama Penulisunclassified
See 1 more Smart Citation